Horizontal distribution of concentrated loads in ComFlor210 composite slabs. (13th September 2017) - Abspoel, Roland; Stark, Jan; Prins, Henk
ABSTRACT: Composite slabs are built up with a thin‐walled cold‐formed steel deck and interconnected with a concrete topping, see Fig .1 a ). Steel decks can be subdivided into two groups, shallow decks and deep decks, see for an example of a deep deck Fig .1 b ). In EN1994 [1] a subdivision is given based on the spacing of the webs. EN1994 covers only narrow spaced webs which are defined by the ratio, where is the width of the upper flange and is the distance between centres of adjacent ribs. The recommended value for the upper limit of this ratio is br / bs, where br is the width of the upper flange and bs is the distance between centres of adjacent ribs. The recommended value for the upper limit of this ratio is br / bs = 0.6. ComFlor210, a deep steel deck produced by Tata Steel UK, has a ratio br / bs = 425/(546 + 54) = 0.71 > 0.6 and is consequently not covered in EN1994. Composite slabs are designed to transfer loads in one direction i.e. the longitudinal direction of the ribs. However when a concentrated load is acting on a rib, part of the load will be distributed to adjacent ribs. The slab is to be considered as an orthotropic plate. In clause 9.4.3 of EN1994‐1‐1 simplified rules are given for the determination of the effective width. However, as explained above, these rules are only applicable to shallow decks. At Delft University of Technology a research project was carried out to gain better understanding in the horizontal distribution of concentrated loads in deep composite slabs – see reference [2]. In the framework of this project a series of three test specimens was tested in the Stevin II laboratory.